Particulate Filler and Discontinuous Fiber Filler Resin Composite's Adaptation and Bonding to Intra-Radicular Dentin - Ferrari Marco; Lettieri Eugenia; Pontoriero Denise Irene Karin; Vallittu Pekka; Cagidiaco Edoardo Ferrari (MDPI, 2025)
The aim of this study was to assess adaptation and bonding to root canal dentin of discontinuous (short) glass fiber-reinforced composite to intra-radicular dentin (DSGFRC).
Methods: Seventy virgin human teeth were extracted and then endodontically treated; then samples were randomly divided into 7 groups (n = 10), based on the materials' combinations as follows: Group 1, a two-bottle universal adhesive + DSGFRC; Group 2, a single-component universal adhesive + DSGFRC; Groups 3 and 4, the same materials of Goups 1 and 2 were used but after cleaning of the canal walls with 17% EDTA and final irrigation with 5.25% NaOCl Ultrasound Activated (UA); Group 5, traditional prefabricated fiber posts were luted after being silanized with G-Multi Primer; Groups 6 and 7, like Group 5 but after ultrasonic irrigation (UA). All sample roots were cut 1 mm thick (n = 10) to be evaluated regarding root canal adaptation using a light microscope and scanning electron microscope (SEM) and push-out bond strength. These results were statistically analyzed by Kruskal-Wallis analysis of variance by ranks. The level of significance was set at p < 0.05.
Results: Bond strength forces varied between 6.66 and 8.37 MPa and no statistically significant differences were recorded among the groups. By microscopic examination, it was noted that ultrasonic irrigation increased the adaptation of the materials to the dentin surface.
Conclusions: Within the limitations of this in vitro study, it may be concluded that when DSGFRC was used for intracanal anchorage in the post-endodontic reconstruction, similar push-out retentive force and strength to those of traditional fiber posts cemented with particulate filler resin composite cements were achieved.